Kolonie : the forgotten empire. - Schellewald, Christian, ....-; Hanenberger, Patrick, ....- (Culver City : Designstudio, 2011)
The Kolonie was a fairly unimportant world at the fringes of the known universe. Although its climate and living conditions make it a habitable environment the immense distance to the central worlds left it provincial and there were no serious plans for any form of colonization. When the first oilfields were discovered, an enormous rush to the Kolonie started immediately. At that time space travel, and any other form of transportation was still completely dependent upon oil. Millions of colonists left their worlds to find their fortunes on the Kolonie. A new class of spaceships was constructed to ferry settlers and supplies to the distant world and bring back oil and oil products in vast quantities. Kapitol, the main city on the Kolonie grew into a huge metropole and for more than a decade it's spaceport was one of the busiest of the entire universe. When oil was finally replaced by other more efficient energy sources importing it from the Kolonie to the main planet ceased to be profitable. The large oil corporations pulled out and shipping to the Kolonie stopped entirely within a short amount of time. Occasionally a government ship from the central world lands on the Kolonie to bring new government troops and officials, spare parts and new technology and sometimes a few passengers. Leaving the Kolonie is difficult and very costly and far too many people are stranded and long to go back to their less remote home planets. But there are still a few adventurers and fortune seekers who manage to travel to the Kolonie which still offers many opportunities. This book is the first chapter in introducing the visually rich world of the Kolonie as well as its inhabitants and technology.